Late Holocene edifice collapse and eruptions of Iriga volcano, Philippines: integrated data from subaerial and lacustrine deposits - Belousov Alexander; Belousova Marina; Listanco Eddie (My University, 2023)
Mount Iriga is a small, dormant stratovolcano of basalt to basaltic andesite composition located in Luzon Island, Philippines. The volcanic edifice includes a well-preserved horseshoe-shaped avalanche scar 2 km across with an adjacent fan of hummocky debris avalanche deposit (DAD) formed by large-scale (1.5 km 3 ) gravitational edifice collapse. To constrain the age of the collapse and determine the character of volcanic activity that followed, we investigated and dated (using the 14 C accelerator mass spectrometry method) paleosoils and organic lake sediments as well as charcoal-containing pyroclastic deposits that closely pre- and post-dated emplacement of the DAD. We found that the collapse of Iriga occurred soon after its 1830 ± 40 BP explosive magmatic eruption (of St. Vincent type) that produced pyroclastic flows of scoriaceous basaltic andesite. In the avalanche-dammed Lake Buhi, the organic bottom sediments started to accumulate at 1780 ± 30 BP, marking the upper age limit of the DAD emplacement. The edifice collapse itself was not contemporaneous with any geologically detectable explosive eruption. After the collapse, a stubby block lava flow with volume of about 0.02 km 3 was extruded inside the horseshoe-shaped avalanche scar. The next eruption of Iriga, which was its only post-collapse explosive eruption, occurred at 1110 ± 30 BP. This phreatomagmatic eruption left a small steep-walled maar-like crater inside the broad avalanche scar in the vent area of the block lava flow. The extrusion of the block lava and the subsequent phreatomagmatic event were the only eruptions of Iriga that occurred after the edifice collapse. Together with the pre-collapse explosive eruption, they comprise the entire eruptive activity of Iriga during the Late Holocene and all occurred during the last 2000 years.
Keywords: Mount Iriga; Large-scale volcanic collapse; Debris avalanche; Eruption; Pyroclastic deposits; Radiocarbon dating; Coring of lake sediments